Impact of hyperventilation and apnea on myocardial oxygenation in patients with obstructive sleep apnea: an oxygenation-sensitive CMR study - Roubille, François; Friedrich, Matthias (Journal of cardiology, 2017)
Background: Oxygenation-sensitive cardiovascular magnetic resonance imaging (OS-CMR) is an emerging technique that can monitor changes in myocardial oxygenation in vivo. Obstructive sleep apnea syndrome (OSAS) is associated with endothelial and microcirculatory dysfunction and increased cardiovascular morbidity and mortality. Little is known about myocardial responses to apnea in patients with OSAS. We hypothesized that the coronary vascular response to hyperventilation and long breath-hold is diminished in patients with OSAS when compared to healthy volunteers. Methods: Twenty-nine OSAS patients and 36 healthy volunteers were prospectively enrolled. All CMR scans were performed on a clinical 3T system. Participants performed a breathing maneuver with 60s of hyperventilation followed by a maximal breath-hold. During the breath-hold, OS-CMR images were continuously acquired and signal intensity changes were measured by a blinded reader. Results: Patients with OSAS were older than healthy volunteers (p<0.01) and presented more co-morbidities; 66% were currently treated with nocturnal positive airway pressure. Compared to healthy participants, the expected increase of myocardial oxygenation during the first 15s of the breath-hold was significantly lower in patients with OSAS (2.6±8.3% vs. 6.7±5.6%; p<0.05), and remained reduced at all time points during the breath-hold. Importantly this result was mainly driven by patients under continuous positive airway pressure (CPAP), suggesting that CPAP might have a greater impact on increase of myocardial oxygenation rather than OSAS itself. Conclusions: The myocardial vascular response to combined breathing maneuvers of hyperventilation followed by voluntary apnea is blunted in patients with obstructive sleep apnea. Clinical studies should now further define the clinical role of oxygenation-sensitive CMR in patients with respiratory disorders.
Available online 30 May 2016
Gesehen am 30.04.2018